Efeitos de um programa de treinamento muscular do assoalho pélvico no pré-operatório de prostatectomia radical sobre incontinência urinária - Oliveira, Melissa Silva de (2024)
Prostate cancer (PC) is the most common type of cancer in the male population. Men over 55 years of age, especially, are more prone to the disease. Radical Prostatectomy (RP) is a curative procedure for cancer patients, however, it has a risk of some complications, such as urinary incontinence (UI). Pelvic Physical Therapy aims to treat the normalization of the function of the pelvic floor muscles. Thus, this study aimed to evaluate the effects of a preoperative pelvic floor muscle training (RAP) program on the UI of patients undergoing surgical treatment for PC. For this, a randomized clinical trial was developed. Data collection was carried out at the Physical Therapy Outpatient Clinic of the University Hospital of Santa Maria. The population consisted of adult and elderly men who underwent surgical treatment for PC. Patients were divided into two groups: GPP (pre- and postoperative group), which underwent PFMT in the pre- and postoperative period; and GP (postoperative group), which underwent PFMT only in the postoperative period. Men aged between 55 and 80 years with localized prostate cancer were included. Patients with metastatic cancer were excluded. The data collection instruments were a sample characterization form; Mini-Mental State Examination to screen for cognitive deficits; International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF), to characterize urinary losses and their impact on quality of life; Male Genital Self-Image Scale, which assesses men's genital self-image; and the Expanded Prostate Cancer Index Composite (EPIC), to assess the impact of radical prostatectomy on the quality of life of patients with PC. Patients with surgery scheduled in less than four weeks were allocated to the GP group, which underwent PFMT only in the postoperative period. Those with surgery scheduled for more than four weeks were placed in the GPP group, undergoing PFMT both pre- and postoperatively. Eight patients were evaluated, 4 in the PG and 4 in the GPP. No statistically significant differences were found between the groups regarding the impact of the preoperative PFMT program on urinary incontinence. Although the ICIQ-SF (p = 0.317) and MGSIS (p = 0.109) scores did not show significant reductions, the EPIC indicated a trend toward improvement, with the total score and the EPIC UI and EPIC UI/O subscales suggesting a possible benefit of the Physical Therapy program on UI in patients undergoing surgical treatment for PC.